Keragaan Produksi dan Pendapatan Petani Kakao Penerap Pengendalian Hama Terpadu (PHT) dan Non Pengendalian Hama Terpadu (PHT) (Studi Kasus di Desa Ataku Kecamatan Andoolo Kabupaten Konawe Selatan) - Suharno, Muhammad; Bahari, Bahari; Abdullah, Weka Gusmiarty (Department of Agribusiness, Halu Oleo University, 2019)
This research aimed was to know The performance of production between cocoa farmers of adopter Integrated Pest Management and non Integrated Pest Management, and The performance of income production between cocoa farmers of adopt Integrated Pest Management and non Integrated Pest Management in the Ataku village, AndooloSub District, South Konawe District. This research was conducted from January to April 2018. The number of cocoa farmers population was in this research to the initial survey was 115 people. The population was grouped into 2 kinds, namely the farmers who adopterIntegrated Pest Management 65 people and farmer of non Integrated Pest Management about 50 people. The number of the sample as determined using proportional stratified random sampling method. The number of samples was determined using Slovin formula, so total samples number were 53 peoples, consist 30 peoples of a cocoa farmer who adopt Integrated Pest Management and 23 peoples of a cocoa farmer who didn't adopt Integrated Pest Management. The result of the research showed that production performance was indicated by the average, production of cocoa farmers who adopt Integrated Pest Management was greater than a cocoa farmer who didn't adopt Integrated Pest Management. The results of the analysis indicated that there was different of production between the farmer who adopts Integrated Pest Management was greater than a cocoa farmer who did not adopt Integrated Pest Management. The revenue performance was indicated by the average income of cocoa farmer who adopts Integrated Pest Management was greater than a cocoa farmer who did not adopt Integrated Pest Management. The result of the analysis shows that there was different of income between the farmer who adopts Integrated Pest Management was greater than a cocoa farmer who did not adopt Integrated Pest Management.